2013
DOI: 10.1111/ijlh.12166
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic detection of blast cells in the cerebrospinal fluid at diagnosis of adult acute lymphoblastic leukemia appears to be associated with adverse prognosis

Abstract: This study suggests that morphologic detection of blast cells in the CSF at diagnosis of adult ALL, regardless of the leukocyte count, is associated with adverse prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…233 One older study 236 showed that patients with blasts had an adverse prognosis, independent of blast count, but therapy was different in that study. Limited data were identified for adult patients with ALL, although one small study 237 suggested that CSF blasts were associated with adverse outcome.…”
mentioning
confidence: 99%
“…233 One older study 236 showed that patients with blasts had an adverse prognosis, independent of blast count, but therapy was different in that study. Limited data were identified for adult patients with ALL, although one small study 237 suggested that CSF blasts were associated with adverse outcome.…”
mentioning
confidence: 99%